Kematian Yesus Kristus bagi Pengampunan - Elisua Hulu (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2019)
Abstract: Without the death of Jesus Christ, there will be no forgiveness of sins nor the eternal salvation for human. The salvation that happens, cannot be separated from the faith of believers to Christ, for what He has done on the cross. By the grace of His forgiveness, the sinful people experience the freedom, which is the restorative key towards the broken relationship between God and human. What Christ has done should be the model for believers in forgivining themselves, also accepting and giving forgiveness. In fact, it needs big effort in forgiving, because of the complex reason. Not only the unbelievers, but also the believers, more than that, God’s servants that have been serving, do not want to give forgiveness to others, which gives impact to the ministry itself. A lot of people are dissapointed, and some leave their faith to Jesus Christ, because they don’t understand the meaning of Christ’s forgiveness through His death in their lives. The unwillingness in forgiving causes the unfinished conflict, and at the end, there will be no harmony between one to another. The forgiveness of God in and through Christ Jesus is totally perfect and enough for human. God’s forgiveness is total, and does’t talk about the sin in the past anymore. The forgiveness that is given by God in and through Jesus Christ is the foundation and model for the forgiveness of believers. The unlimited and perfect forgiveness of Jesus Christ enabled believers in forgiving others.